The Psychodynamics of Salafi-Jihadism - Alhnaity, Hisham Odeh (Dirasat: Human and Social Sciences, 2025)
Objectives: This study sheds light on the psychodynamics underlying the intellectual extremism and violent behavior of four influential Jordanian Salafi-Jihadist figures, namely Abdallah Azzam (a proponent of global Jihadism and the founder of “the Base” in Afghanistan, later named “al-Qaida”), Abu Mohammad Al-Maqdisi (a well-known Jihadi intellectual and a leading theorist of radical Islamic thought), Al-Zarqawi (a former leader of al-Qaida in Iraq (AQI) whose ideas paved the way for ISIS), and Abu Qatada Al-Felistini (the founder of the logistic and ideological hub in London supporting al-Qaida). The study seeks to analyze the origins, development, dissemination, and impact of their ideologies. Methods: The study employs a qualitative methodological analysis, drawing on insights from cognitive psychology, motivational psychology, perspectives theory, and behavioral economics. Results: The findings reveal that Salafi-Jihadist elites play pivotal roles in numerous contemporary intra-state conflicts. Comprehending the violent actions of prominent ideologues requires an understanding of their psychodynamics and the Jihadi narrative. The study shows that their deep-seated feelings, demands, and desires affect their decision-making and shape their strategic narrative. Such understanding is instrumental in countering extremist narratives and elucidating the root causes of violence perpetrated by their followers. Conclusion: The study demonstrates that long-term conflict resolution is impossible without taking into account the religious identity and ideological discourse of Salafi-Jihadist groups, particularly their symbolic leaders. Such knowledge is essential for anticipating the intentions or behaviors of an adversary and implementing effective countermeasures.